Analogy of Law as a Form of Judicial Precedent - Yu. G. Izotov (Теоретическая и прикладная юриспруденция)
This study is devoted to the problem of the relationship between judicial precedent and the analogy of law. The author, studying the nature of judicial law-making, notes that law-making activity is inherent in any body of the state, if the constitution does not directly prohibit it from creating new norms. The article provides a critique of the approach to understanding the analogy of law as a way of applying law. The author notes that it is impossible to apply abstract principles directly, the court, like a legislator, must first formulate a specific provision (rule of law) on the basis of them, and then apply it. Hence it is concluded that the analogy of law is a form of judicial precedent. Normative substantiation of the possibility of Russian courts to create law requires an answer to the question about the characteristics of the judicial norm and its place in the system of sources of modern Russian law. The author comes to the conclusion that the judicial norm is causal, special and retroactive, and it can take any place, with the exception of the provisions of the Constitution of the Russian Federation, which can only be changed through the direct will of the people (chapters 1, 2, 9). The article also proposes to supplement the institution of analogy of law with norms on the mandatory request of the court considering the case to the Presidium of the Supreme Court of the Russian Federation on the creation of a judicial norm.